Pendidikan Ahlak; Perpektif Ahmad Amin dalam karyanya Al Ahlaq - Raikhan Raikhan (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2020)
Abstract: In this paper, the author will discuss one side of moral education that is often overlooked in the planning, development and evaluation of moral education programs, namely developing a school culture that has the spirit of shaping morality in an Islamic perspective represented by one of the ahlak figures. More specifically, the author will discuss how to develop a morality culture in the school environment, understand the challenges, find the implementation of effective strategies for developing this culture for the formation of national morality. The author tries to dig back into Ahmad Amin's thoughts in his work, al ahklaq, to ​​answer the problem of ahlak. As for the morality itself, Ahmad Amin provides a definition as an accustomed will, so that education must be taught with habituation, exemplary, and knowledge of morality. Regarding the value of superior behavior according to Amin, including: honest, brave, simple, fair, confident, obedient, take advantage of time, and like to help